Spatial variation and potential ecological risk assessment of trace elements in the sediments of Chaohu Lake in China - ChangLi Hu; Ting Hu; Long Liang (Journal of Freshwater Ecology)
Chaohu is a large freshwater lake. It plays an essential part in agriculture, life, and part of the industry. This study analyzed the heavy metals contents of copper (Cu), zinc (Zn), cadmium (Cd), mercury (Hg), arsenic (As), chromium (Cr), nickel (Ni), and lead (Pb) in sediments of the Chaohu Lake using inductively coupled plasma mass spectrometry. The distribution of some potential hazardous trace element in Chaohu Lake in the order as Zn (44.04 mg kg−1)>Cu (28.62 mg kg−1)>Cr (27.39 mg kg−1)>Pb (16.71 mg kg−1)≈Ni (16.22 mg kg−1)>As (5.89 mg kg−1)>Cd (0.14 mg kg−1)>Hg (0.04 mg kg−1). The results indicated that the selected heavy metals in the lake were practically uncontaminated, and the levels of selected potential hazardous elements varied from different sampling sites. Correlation analysis indicated that the selected potential hazardous element pollutant has co-contamination also occurs in sediments. However, in the center of Chaohu Lake, the primary contributor to the ecological risk was Cd (41%) and Hg (40%). Based on the PERI, the total potential ecological risk of selected heavy metals in the sediments of Chaohu Lake was light-contaminated.